Appraisal of oral lesions status of HIV/AIDS patients in South Western Uganda - Ezera Agwu (Brazilian Journal of Oral Sciences, 2016)
Aim: To establish a regional surveillance data that may contribute to improvement of oral health prevention/control programs in South Western Uganda. Methods: Using WHO guidelines, HIV-associated oral lesions were identified among 605 HIV/AIDS patients (469 females and 136 males), selected at random from 4 districts of South Western Uganda. Pearson’s Chi square test of independence (α=0.01), was used to compare results. Results: Prevalence of oral lesions was 73.2%. Pseudomembranous Candidiasis (PC) showed the highest overall prevalence of 71.1% (34.9% single and 36.2% mixed); followed by 39.9% prevalence of Erythematous Candidiasis (EC) (13.2%) single; 26.7% mixed) and 18.8% prevalence of Angular Chelitis (AC) (3.1% single and 15.7% mixed). There was: 23.6% co-infection of PC and EC; 12.6% PC and AC, 3.1% were EC and AC, and 17.0% intra-oral pigmentation. Prevalence of oral lesions was significantly (p<0.01) dependent on host pre-exposure to antimicrobials. Conclusions: Oral infections are still highly prevalent among the studied HIV/AIDS patients in South Western Uganda. This observation may be due to inadequate antimicrobial agents and oral/dental care. There’s urgent need to train primary health care workers in management of oral lesions associated with HIV/AIDS. More studies are needed to evaluate HIV/AIDS oral lesions in the populace.